The study of traditional malay decorations & wood carving : a case study of the Istana Kenangan, Kuala Kangsar, Perak. / Afzanizam Muhammad ... [et al.] - Muhammad, Afzanizam; Talib, Anuar; Abdul Rashid, Mohd Sabrizaa; Mohamed, Abdul Hamid; Rasol, Noor Faiza (2012)
Wood carving in Malaysia started as early 14th century. But most of the earlier works do not exist today because of the wood properties itself that are not durable due to weather, moisture and fire. Conservation of traditional timber buildings and documentation is needed as a step to preserving this inheritance. The Istana Kenangan (Memory Palace) in Kuala Kangsar, Perak is built mainly out of timber and enveloped by kelarai walls (Traditional bamboo wall) . The significance of the building is not just as a typical traditional building but it is also a part of the Perak state history during the reign of the Sultan Iskandar Shah Sultanate (1918-1938). The aim and objectives of this study is to identify the components of the palace that has a traditional decorations and wood carving motifs in order to establish the inventory of patterns on Istana Kenangan. The inventory of the patterns and motifs on Istana Kenangan is supported with measured drawings on the plans, elevations and decorative components detail drawing. The "case study method‟ is applied in this research. At the end of this research the uniqueness of this building is revealed and the significance of this palace is realized to be more important to conserve traditional architecture especially for the Perak regional style. The inventory produced can ensure this inheritance will remain for future generation and further studies.